Reconstructing past cultural landscape and human impact using pollen and plant macroremains - Sadori, L.; MERCURI, A. M.; MARIOTTI LIPPI, M. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2010)
Abstract Three examples of plant landscape shaping, carried out by Iron Age populations living in different geographical areas, are presented. The examples differ in population type (Garamantes, Etruscans, and Romans), archaeological context (settlement, necropolis, furnace, port), and area of plant exploitation (respectively, Fezzan ? Libyan Sahara and Tuscany, Latium ? central Italy). The leitmotiv of the three parallel investigations highlighted that humans induced clear changes in plant cover modifying the quantitative ratio among native elements and spreading the plants of economic interest even outside of their natural habitats. Micro- and macroremain analyses once more enhanced that landscape reconstruction depends on both wild and cultivated plants, and that the cultural plant landscape is composed of a complex mixture of indigenous and exotic elements. Archaeobotany results in great help in reviewing ancient prejudices, rewriting history in a modern ecological view, also discovering a different role in the landscape evolution of past civilizations. In this light, the Garamantes deeply transformed the oases in agrarian producer sites, and the Etruscans, in the area of the Gulf of Follonica, modified the previous forest vegetation, probably enhancing the xeric features. The Romans, believed as the main creators of the environmental changes in the Mediterranean basin, surprisingly did not produce consistent plant changes in the area of the Tiber delta, in the surroundings of the imperial port of Rome, during the first century AD.
doi: 10.1080/11263504.2010.491982doi: 10.1080/11263504.2010.491982The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Archaeobotany; cultural landscape; Etruscans; Garamantes; Iron Age; macroremains; pollen; Romans

The agricultural consequences of colonial contacts on the Iberian Peninsula in the first millennium b.c - Buxó, Ramon (Vegetation History and Archaeobotany, 2007)
The Iron Age archaeobotanical record on the Iberian Peninsula shows how the Phoenician and Greek colonisers caused the indigenous Iberians to change the management of the agricultural resources and the crops which they grew. These colonisers also brought about the development of viticulture and olive cultivation. The importance of agricultural products in the trade network which was stimulated by the colonisers may have encouraged new farming systems, as well as surplus capacity in the native agriculture in the region.
Keywords: á agricultural products á; Agricultural products; Archaeobotanical record; archaeobotanical record á; c; cal b; Early Iron Age; from the ninth century; Iron Age; Phoenician and Greek colonisation; to the romanisation of; Trade network; trade network á early

The agricultural consequences of colonial contacts on the Iberian Peninsula in the first millennium b.c - Buxó, Ramon (Vegetation History and Archaeobotany, 2007)
The Iron Age archaeobotanical record on the Iberian Peninsula shows how the Phoenician and Greek colonisers caused the indigenous Iberians to change the management of the agricultural resources and the crops which they grew. These colonisers also brought about the development of viticulture and olive cultivation. The importance of agricultural products in the trade network which was stimulated by the colonisers may have encouraged new farming systems, as well as surplus capacity in the native agriculture in the region.
Keywords: á agricultural products á; Agricultural products; Archaeobotanical record; archaeobotanical record á; c; cal b; Early Iron Age; from the ninth century; Iron Age; Phoenician and Greek colonisation; to the romanisation of; Trade network; trade network á early